2013
DOI: 10.1097/mao.0b013e31827de4dd
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Osseointegrated Implant Surgery Without Skin Thinning in Children

Abstract: The percutaneous osseointegrated implantation technique without skin thinning that has recently been implemented in adults is also beneficial for children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
14
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 19 publications
(16 reference statements)
4
14
0
Order By: Relevance
“…We did observe a trend toward fewer complications (17%) when a no soft‐tissue reduction technique was used. This is consistent with several studies that suggest a lower rate of complications when a simplified surgical technique without soft tissue reduction is used …”
Section: Discussionsupporting
confidence: 92%
“…We did observe a trend toward fewer complications (17%) when a no soft‐tissue reduction technique was used. This is consistent with several studies that suggest a lower rate of complications when a simplified surgical technique without soft tissue reduction is used …”
Section: Discussionsupporting
confidence: 92%
“…However, variable degrees of inflammation or infection around the abutment are not uncommon . Certain complications reported from bone conduction implant surgeries, such as flap necrosis and numbness and/or pain around the implant, are related to extensive tissue removal . In addition, soft tissue reduction has the cosmetic drawback of leaving a hair‐free “divot” area around the abutment.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Certain complications reported from bone conduction implant surgeries, such as flap necrosis and numbness and/or pain around the implant, are related to extensive tissue removal. [5][6][7] In addition, soft tissue reduction has the cosmetic drawback of leaving a hair-free "divot" area around the abutment. Therefore, from both a medical and esthetic perspective, leaving the skin intact may provide significant advantages if soft tissue stability can be guaranteed.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the skin thinning and hypertrophic scar tissue could reduce blood transport, thus potentially hampering the local immunological responses of importance in the healing procedure and in peri-implant infections (21). Recent studies indicate that the omission of skin thinning may be preferable to any reduction of the subcutis, as it does not augment skin problems clinically or histologically and it allows for a better aesthetic outcome (1,4,6,22). These results were reinforced in the current study, as no increased rate of skin-related problems was observed in the test group 5 years after implantation.…”
Section: Discussionmentioning
confidence: 98%
“…Periimplant infections, the most common sequelae from the traditional procedure, were also reduced in number after the non-skin thinning procedure. Notably, BAHD implantation without skin thinning has been proven useful in both adults and children (1,6). Previous studies of this new technique, however, have been limited to short follow-up periods.…”
mentioning
confidence: 98%